An open‐source biomass pyrolysis reactor. (11th September 2017) - Woolf, Dominic; Lehmann, Johannes; Joseph, Stephen; Campbell, Christopher; Christo, Farid C.; Angenent, Largus T.
Abstract: Despite its long history of technological development, much charcoal production still relies on polluting and inefficient technologies utilizing traditional kiln designs. In addition to the need for improved charcoal production systems, the growing interest globally in pyrolysis of biomass to generate biochar as a soil fertility improver and for climate change mitigation may drive an increasing demand for such technologies. Accordingly, there is a clear need in developing countries for access to safe, affordable, and efficient open‐source designs and technology that can be fabricated locally. The design described here includes computational fluid dynamics modeling which demonstrated that the design exhibits a stable flow and combustion pattern. A hazard and operability (HAZOP) study, mass and energy modeling, and costing of all components and fabrication were also conducted for a prototype kiln that will accept up to 250 kg biomass h ‐1 . Fabrication and installation costs were estimated using actual commercial quotations based on detailed engineering drawings and design, and were found to be 580 000 for a 250 kg h ‐1 unit. We therefore find that this pyrolysis system promises to be economical on a small scale. It can utilize waste lignocellulosic materials for feedstock, thus alleviating demand pressure on woodlands to provide feedstocks. It was, therefore, concluded that the pyrolysis unit described here promises to provide an affordable and efficient open‐source design that can be fabricated locally in developing countries without licensing restrictions or royalties. © 2017 The Authors Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd